2004
DOI: 10.1128/jb.186.10.3097-3107.2004
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Protein Signatures Provide Molecular Markers and Evidence for the Monophyletic Nature of the Deinococcus-Thermus Phylum

Abstract: The Deinococcus-Thermus group of species is currently recognized as a distinct phylum solely on the basis of their branching in 16S rRNA trees. No unique biochemical or molecular characteristics that can distinguish this group from all other bacteria are known at present. In this work, we describe eight conserved indels (viz., inserts or deletions) in seven widely distributed proteins that are distinctive characteristics of the DeinococcusThermus phylum but are not found in any other group of bacteria. The ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 43 publications
(81 reference statements)
0
25
0
Order By: Relevance
“…Multiple sequence alignments for these and many other proteins that have been created in our earlier work (Griffiths & Gupta, 2004;Gao & Gupta, 2005) were visually inspected to identify any conserved indel that was restricted to either all or specific groups of the clostridia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sequence alignments for these and many other proteins that have been created in our earlier work (Griffiths & Gupta, 2004;Gao & Gupta, 2005) were visually inspected to identify any conserved indel that was restricted to either all or specific groups of the clostridia.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum-likelihood (ML) analysis was carried out using the WAG+F model with gamma distribution of evolutionary rates with four categories using the TREE-PUZZLE program with 10 000 puzzling steps (Schmidt et al, 2002). Maximum-parsimony (MP) trees based on 1000 bootstrap replicates were computed using the MEGA 4.1 program (Tamura et al, 2007).Identification of conserved indels specific to the clostridia.Multiple sequence alignments for these and many other proteins that have been created in our earlier work (Griffiths & Gupta, 2004;Gao & Gupta, 2005) were visually inspected to identify any conserved indel that was restricted to either all or specific groups of the clostridia. …”
mentioning
confidence: 99%
“…When an indel is present in only a single species, it is difficult to determine whether it is unique to that particular species or whether it is a shared characteristic of related bacteria. However, based upon our experience with other conserved indels, it was reasoned that if the indel was present in a conserved region there was a good chance that it might also be present in other related bacteria (Gupta, 2000(Gupta, , 2004, 2004a. Based on this rationale, the sequence alignments of different proteins constructed in our earlier work were examined to identify any indel in a conserved region that was present uniquely in 'A.…”
Section: Identification and Characterization Of Conserved Indels Specmentioning
confidence: 99%
“…Rare genomic changes such as conserved inserts and deletions (indels; also referred to as signature sequences) in gene/protein sequences that are restricted to particular groups of bacteria provide a powerful and as yet largely untapped resource for developing definitive molecular markers that can clearly distinguish and circumscribe the major groups within the Bacteria (Gupta, 1998;Rokas & Holland, 2000;Coenye et al, 2005). In our recent work, a large number of conserved indels in diverse proteins has been identified that are distinctive characteristics of various other bacterial groups such as the Proteobacteria (Gupta, 2000), Chlamydiales , Cyanobacteria (Gupta et al, 2003), the Fibrobacter-ChlorobiBacteroidetes (Gupta, 2004), Alphaproteobacteria (Gupta, 2005), Actinobacteria and the Deinococcus-Thermus groups (Griffiths & Gupta, 2004a). These taxon-or phylum-specific genetic changes provide valuable molecular markers for taxonomic as well as genetic and biochemical characterization of these groups of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Phylogenetically, the Deinocuccus-Thermus group diverged at an early stage of the bacterial evolution. 1,2) T. thermophilus biosynthesizes lysine not through the diaminopimelate but through the aminoadipate pathway. [3][4][5] D. radiodurans has genes all homologous to T. thermophilus lysine biosynthetic genes.…”
mentioning
confidence: 99%